2012
DOI: 10.1534/g3.111.000869
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Survey of Large Rare Copy Number Variants in Alzheimer’s Disease Among Caribbean Hispanics

Abstract: Recently genome-wide association studies have identified significant association between Alzheimer's disease (AD) and variations in CLU, PICALM, BIN1, CR1, MS4A4/MS4A6E, CD2AP, CD33, EPHA1, and ABCA7. However, the pathogenic variants in these loci have not yet been found. We conducted a genome-wide scan for large copy number variation (CNV) in a dataset of Caribbean Hispanic origin (554 controls and 559 AD cases that were previously investigated in a SNP-based genome-wide association study using Illumina Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 50 publications
5
54
1
Order By: Relevance
“…However, the role of copy number variations (CNVs) and recessive inheritance (e.g. estimated based on runs of homozygosity) need further exploration (Ghani, et al, 2012, Ghani, et al, 2013a). …”
Section: Introductionmentioning
confidence: 99%
“…However, the role of copy number variations (CNVs) and recessive inheritance (e.g. estimated based on runs of homozygosity) need further exploration (Ghani, et al, 2012, Ghani, et al, 2013a). …”
Section: Introductionmentioning
confidence: 99%
“…CHRNA7 was found to be one of the genes with suggestive significance (Heinzen et al, 2010). A similar study on Caribbean Hispanics revealed nominal association at Chr15q11.2 (Ghani et al, 2012) encompassing five genes. In a study on the AD neuroimaging initiative samples, significant higher burden of CNV-region deletions was found in mild cognitive impairment (MCI) and AD cases compared to controls (Guffanti et al, 2013).…”
Section: Cnv Studiesmentioning
confidence: 75%
“…Due to the complexity of sequence alterations caused the mechanistic links between structural variants and phenotypes of interest are often difficult to assess and prove. Apart from the CNVs described in CR1 [71] and a ∼470 kb duplication on chromosome 15q11.2 encompassing five genes (TUBGCP5, CYFIP1, NIPA2, NIPA1 and WHAMML1) [122], no structural variants have been reported in AD. However, this is a rapidly developing field and continues to be an area of study.…”
Section: Rare Variants Associated With Admentioning
confidence: 99%